A toxicological evaluation of geranylgeraniol - Preece, Kayla; Glávits, Róbert; Foster, John R.; Murbach, Timothy; Endres, John R.; Hirka, Gábor; Vértesi, Adél; Béres, Erzsébet; Szakonyiné, Ilona Pasics (Regulatory toxicology and pharmacology, 2021)
Geranylgeraniol (GGOH) is an isoprenoid compound found in annatto seeds and an intermediate of the mevalonate pathway found within organisms serving various functions. Toxicological studies on its safety profile are not readily available. To assess the safety of GGOH, a molecularly distilled, food grade annatto oil, consisting of approximately 80% trans-GGOH, was subjected to a bacterial reverse mutation test, an in vitro mammalian chromosomal aberration test, and an in vivo mammalian micronucleus test in order to investigate its genotoxic potential and a 90-day repeated-dose oral toxicity study in rats in order to investigate its potential subchronic toxicity and identify any target organs. No evidence of mutagenicity or genotoxic activity was observed under the applied test systems. In the 90-day study, male and female Hsd. Han Wistar rats were administered daily doses of 0, 725, 1450, and 2900 mg/kg bw/day by gavage. Treatment-related adverse effects were observed in the forestomach at all dose levels and in the liver at the intermediate- and high-dose levels. Based on these results, the lowest observed adverse effect level (LOAEL) for local effects and the no observed adverse effect level (NOAEL) for systemic effects were determined as 725 mg/kg bw/day. •Geranylgeraniol is an isoprenoid found in annatto (Bixa orellana) seeds.•Geranygeraniol was not mutagenic or clastogenic in vitro.•Geranygeraniol showed no in vivo genotoxicity.•The no observed adverse effect level for systemic toxicity in the 90-day study was 725 mg/kg bw/day.